Nanocarriers for photodynamic-gene therapy - de Santana, Willian Max O.S. [UNESP]; Surur, Amanda Koberstain [UNESP]; Momesso, Vinícius Medeiros [UNESP]; Lopes, Pedro Monteiro [UNESP]; Santilli, Celso V. [UNESP]; Fontana, Carla Raquel [UNESP] (Elsevier, 2023)
The use of nanotechnology in medicine has important potential applications, including in anticancer strategies. Nanomedicine has made it possible to overcome the limitations of conventional monotherapies, in addition to improving therapeutic results by means of synergistic or cumulative effects. A highlight is the combination of gene therapy (GT) and photodynamic therapy (PDT), which are alternative anticancer approaches that have attracted attention in the last decade. In this review, strategies involving the combination of PDT and GT will be discussed, together with the role of nanocarriers (nonviral vectors) in this synergistic therapeutic approach, including aspects related to the design of nanomaterials, responsiveness, the interaction of the nanomaterial with the biological environment, and anticancer performance in studies in vitro and in vivo.
Keywords: Anticancer; Combination therapy; Gene therapy; Nanoparticles; Nonviral vectors; Photodynamic therapy